Recognition of cisplatin-damaged DNA by p53 protein: critical role of the p53 C-terminal domain - Pivonková, Hana; Brázdová, Marie; Kaspárková, Jana; Brabec, Viktor; Fojta, Miroslav (Biochemical and biophysical research communications, 2006)
It was shown previously that the p53 protein can recognize DNA modified with antitumor agent cisplatin (cisPt-DNA). Here, we studied p53 binding to the cisPt-DNA using p53 deletion mutants and via modulation of the p53-DNA binding by changes of the protein redox state. Isolated p53 C-terminal domain (CTD) bound to the cisPt-DNA with a significantly higher affinity than to the unmodified DNA. On the other hand, p53 constructs involving the core domain but lacking the C-terminal DNA binding site (CTDBS) exhibited only small binding preference for the cisPt-DNA. Oxidation of cysteine residues within the CD of posttranslationally unmodified full length p53 did not affect its ability to recognize cisPt-DNA. Blocking of the p53 CTDBS by a monoclonal antibody Bp53-10.1 resulted in abolishment of the isolated CTD binding to the cisPt-DNA. Our results demonstrate a crucial role of the basic region of the p53 CTD (aa 363-382) in the cisPt-DNA recognition.
Keywords: Tumor Suppressor Protein p53; sekvenční delece; DNA Damage; cisplatina; Protein Structure, Tertiary; vazebná místa; Cisplatin; Substrate Specificity; vazba proteinů; Antibodies, Monoclonal; terciární struktura proteinů; DNA; oxidace-redukce; poškození DNA; Oxidation-Reduction; nádorový supresorový protein p53; monoklonální protilátky; substrátová specifita; Sequence Deletion; Protein Binding; Binding Sites